2016
DOI: 10.1111/epi.13430
|View full text |Cite
|
Sign up to set email alerts
|

5‐Hydroxytryptophan, a precursor for serotonin synthesis, reduces seizure‐induced respiratory arrest

Abstract: Summary Objective The DBA/1 mouse is a relevant animal model of sudden unexpected death in epilepsy (SUDEP), as it exhibits seizure-induced respiratory arrest (S-IRA) evoked by acoustic stimulation, followed by cardiac arrhythmia and death. Defects in serotonergic neurotransmission may contribute to S-IRA. The tryptophan hydroxylase-2 (TPH2) enzyme converts L-tryptophan to 5-hydroxytryptophan (5-HTP), a precursor for central nervous system (CNS) serotonin (5-HT) synthesis; and DBA/1 mice have a polymorphism t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(90 citation statements)
references
References 44 publications
6
84
0
Order By: Relevance
“…Other studies have also demonstrated that S-IRA is the primary event causing sudden death following evoked generalized seizures in most cases (Buchanan et al, 2014; Faingold et al, 2010; Zhang et al, 2016). Therefore, S-IRA is a likely contributor to some SUDEP cases.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Other studies have also demonstrated that S-IRA is the primary event causing sudden death following evoked generalized seizures in most cases (Buchanan et al, 2014; Faingold et al, 2010; Zhang et al, 2016). Therefore, S-IRA is a likely contributor to some SUDEP cases.…”
Section: Discussionmentioning
confidence: 90%
“…DBA/1 mice were originally purchased from Envigo (Indianapolis, IN) and were housed and bred in the animal facility at Massachusetts General Hospital under a temperature- and humidity-controlled environment (12-h light/dark cycle), provided with rodent food and water ad libitum . DBA/1 mice were “primed” by daily exposure to acoustic stimulation using an electric bell (96 dB SPL, UC4-150, Zhejiang People’s Electronics, China) for 3–4 days, starting from postnatal day 26–28, to establish consistent susceptibility to audiogenic seizures (AGSz) and S-IRA (Zhang et al, 2016). The same acoustic stimulus parameters were used in priming and induction of AGSz.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The operational criteria for S-IRA were defined by the appearance of a deep respiratory gasp and relaxation of the pinnae determined visually, which were invariant indicators in previous studies that S-IRA had begun and death was imminent [8]. Although S-IRA was behaviorally determined by qualitative (visual) breathing assessment, our previous quantitative studies using plethysmography indicated that S-IRA leads to terminal asystole and death in DBA/1 mice [32]. Resuscitation was accomplished by placing the outflow polyethylene tube (4.4 mm external diam.)…”
Section: Methodsmentioning
confidence: 99%